Uji Efektivitas Protein Hidrolisat Ikan Cucut (Carcharhinus sp.), Naktar dan Beauveria bassiana Untuk Mengendalikan lalat Buah (Bactrocera dorsalis complex) (Diptera: Tephtritidae) di Laboratorium - Immanuel Sembiring; Maryani Cyccu Tobing; Lahmuddin Lubis; Mirasiska Tarigan (Jurnal Agroekoteknologi, 2014)
The effectivity of swordfish protein hydrolysis, nectar and biological agent (Beauveria bassiana) tocontrol fruit flies (Bractocera dorsalis complex).The objectives of research was to study the abilityof protein hydrolysis swordfish, nectar and Beauveria bassiana to control fruit flies (Bractoceradorsalis complex). In the research was held at Laboratory of Agricultural Research andDevelopment of Fruit Crops Experimental Garden Plants Berastagi, Kecamatan Dolat Rayat,Kabupaten Karo (in 1.340 meters). The method used Randomized Complete Design with twofactors and three replications. The first factor was protein hydrolysis concentrate (0 % /liter nectar +Beauveria bassiana, 25 % /liter of nectar + Beauveria bassiana,50 % /liter of nectar + Beauveriabassiana, 75 % /liter of nectar + Beauveria bassiana, 100 % /liter of nectar hydrolysis + Beauveriabassiana) and the second factor was infection technic (male and female feed, male feed and femalefeed). The results showed that infection technic and protein hydrolysis concentrate significantlyeffected the percentage of fruit fly mortality. The highest percentage (93,33%) 75 % /liter of nectar+ Beauveria bassiana on male and female feed, and the lowest (70,00%) 50 % /liter of nectar +Beauveria bassiana on male feed.Keywords :Fruit fly, protein hydrolysis, nectar, Beauveria bassiana